What Is Not Sacred? African Spirituality - Magesa, Laurenti (Orbis Books, 2013)
Did Christianity replace traditional African religion with the arrival of European missionaries in past centuries? Or did sub-Saharan African cultures persist in maintaining their religious worldviews even after accepting the salvific message of Christianity? In this compelling book, noted scholar Laurenti Magesa argues that despite missionary Christianity's refusal to acknowledge the worth of traditional African religious culture, the incarnational spirituality of those cultures remains vibrant and visible today, and has much to offer and teach other cultures, both Christian and not. When we admit that, in fact, all is sacred, we are challenged to reevaluate our relationships with each other, with other cultures, with God, and with the environment. Divided into two parts, Magesa's book first explores how traditional African spirituality plays out in human understanding and influences relationships between human beings and their environment. In the second half of the book, he connects traditional African spirituality with life today, showing its value for interreligious dialogue, political governance, the quest for peace and justice, and Christian spirituality in a globalized world.